A novel multifunctional β-cyclodextrin polymer as a promising sorbent for rapid removal of methylene blue from aqueous solutions. (1st May 2023) - Lagiewka, Jakub; Nowik-Zajac, Anna; Pajdak, Anna; Zawierucha, Iwona
Abstract: Production wastewater has evolved with dye and printing technology to become one of the major sources of soil and water contamination. The majority of dyes are carcinogenic, teratogenic, and mutagenic compounds. As a result, dealing with the dye in the wastewater is a critical issue. Insoluble polymers of β-cyclodextrin (β-CD), an inexpensive, sustainably produced macrocycle of glucose, have potential to remove dyes from water/wastewater via sorption due to formation of well-defined host–guest complexes. A novel polymeric sorbent based on cyclodextrin was successfully synthesized in a one-step reaction with few reagents. The polymer is characterized by multifunctionality and cross-linked network structure. The sorption studies aimed at the removal of methylene blue (MB) from aqueous solutions. The dominant model was Langmuir isotherm which indicated a sorption capacity of 96.15 mg/g. The rapid removal has already been obtained after 1 min, around 84 % of efficiency. The molecular mechanism of MB sorption by poly(β-CD-BPDA) network is found mostly on the electrostatic interactions and partially on the inclusion of complexation inside supramolecular pores based on cyclodextrins' cavities, hydrogen bonding and slightly π-stacking. The presented polymer seems to be a promising sorbent for the removal of hazardous organic pollutants from water/wastewater. Graphical abstract: Unlabelled Image